Perbandingan analisis sentimen pada aplikasi SIREKAP dengan aplikasi SITUNG di media sosial X menggunakan algoritma Support Vector Machine - Taufik Akbar; Rahmi Imanda (The Indonesian Journal of Computer Science, 2024)
Indonesia is a democratic system, the election must through PEMILU. Until now, the KPU has made 2 applications for the elections, the Vote Selection Information System (SITUNG) and the Electronic Recapitulation Information System (SIREKAP). However, it turns out that the implementation of elections with these two applications raises various kinds of sentiments from the community. This research aims to determine the public sentiment towards SITUNG and SIREKAP and whether the number of negative sentiments of SIREKAP is more than SITUNG. This research takes data from X social media and uses SVM for algorithm. The number of sentiments used for SITUNG is 1469 which consists of 832 positive sentiments and 637 negative sentiments, then for SIREKAP is 1897 which consists of 1092 positive sentiments and 805 negative sentiments. The results of the precision, recall and f1-score values on SITUNG are around 70%, 69%, 69% while SIREKAP is around 67%, 66%, 66%.